(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This study assessed the effects of safflower oil on cytokine dynamics, angiogenesis factors, and metabolic regulators in an experimental rat model of toxic hepatitis. IL-1β levels were 1.47-fold higher on day 7 and 2.04-fold higher on day 14 compared to intact animals (p<0.05), indicating reduced inflammatory activity. IL-4 concentration exceeded control values 2.19- and 2.06-fold on days 7 and 14, respectively (p<0.05), reflecting stimulation of regenerative processes. IL-6 showed a 1.34-fold and 1.56-fold increase (p<0.05), while TNFα rose 2.12- and 2.59-fold (p<0.05), demonstrating immune activation. VEGF-A levels increased 3.63-fold on day 7 and 2.54-fold on day 14 (p<0.05), confirming angiogenesis induction. βKlotho levels were 4.47-fold and 2.14-fold higher on days 7 and 14 (p<0.05), indicating prolonged cytoprotective effects. These findings confirm the strong immunomodulatory and hepatoprotective potential of safflower oil, mediated through cytokine modulation and enhanced regenerative mechanisms.